Inhibitors of the NMDA-Nitric Oxide Signaling Pathway Protect Against Neuronal Atrophy and Synapse Loss Provoked by l-alpha Aminoadipic Acid-treated Astrocytes. (10th November 2018) - David, J.; O'Toole, E.; O'Reilly, K.; Thuery, G.; Assmann, N.; Finlay, D.; Harkin, A.
Highlights: Media from L-AAA-treated astrocytes decreases complexity of cultured neurons. L-AAA reduces GFAP expression, and mitochondrial respiration in astrocytes. NMDA-R/NO inhibitors protect against loss of neuronal complexity. Delivery of L-AAA to the pre-limbic cortex of mice increases dendritic spines. ZL006 decreases dendritic spines in the pre-limbic cortex of L-AAA-treated mice. Abstract: The impact of treating astrocytes with the astrocytic toxin l-alpha amino adipic acid (L-AAA) on neuronal outgrowth, complexity and synapse formation was assessed, using a model of astrocyte-neuronal interaction. Treatment of rat primary cortical neurons with conditioned media (CM) derived from astrocytes treated with L-AAA reduced neuronal complexity and synapse formation. L-AAA provoked a reduction in the expression of glial fibrillary acid protein (GFAP) and a reduction in ATP-linked mitochondrial respiration in astrocytic cells. As the NMDA-R/PSD-95/NOS signaling pathway is implicated in regulating the structural plasticity of neurons, treatment of neuronal cultures with the neuronal nitric oxide synthase (nNOS) inhibitor 1-[2-(trifluoromethyl)phenyl] imidazole (TRIM) [100 nM] was assessed and observed to protect against L-AAA-treated astrocytic CM-induced reduction in neuronal complexity and synapse loss. Treatment with the NMDA-R antagonist ketamine protected against the CM-induced loss of synapse formation whereas the novel PSD-95/nNOS inhibitors 2-((1H-benzo[d] [1, 2, 3]triazol-5-ylamino) methyl)-4, 6-dichlorophenol (IC87201) and 4-(3, 5-dichloro-2-hydroxy-benzylamino)-2-hydroxybenzoic acid (ZL006) protected against synapse loss with partial protection against reduced neurite outgrowth. Furthermore, L-AAA delivery to the pre-limbic cortex (PLC) of mice was found to increase dendritic spine density and treatment with ZL006 reduced this effect. In summary, L-AAA-induced astrocyte impairment leads to a loss of neuronal complexity and synapse loss in vitro and increased dendritic spine density in vivo that may be reversed by inhibitors of the NMDA-R/PSD-95/NOS pathway. The results have implications for understanding astrocytic-neuronal interaction and the search for drug candidates that may provide therapeutic approaches for brain disorders associated with astrocytic histopathology.